Workshop on Environmental Compassion and Energy-Saving Character Development - Maleiva, Lalak Tarbiyatun Nasyin; Nugraheni, Putranty Widha; Putra, Leonardus Sandy Ade; Kusumawardhani, Eka; Abidin, Zainal (Institut Teknologi Nasional, Bandung, 2024)
The cultivation of strong character in schools can be achieved through character education. One promising approach to cultivating a deep affection for the environment is through the Workshop on Environmental Compassion and Energy Savings Character Development. Hence, it is essential to educate individuals about the implementation of the 4R (Reduce, Reuse, Repair, Recycle) principles and minimize energy when utilizing electronic devices in households and schools. By nurturing a foundational awareness of energy conservation and environmental consciousness at Bruder Melati Pontianak Elementary School, it is expected that the teachers will be able to impart this knowledge. Through the implementation of dissemination, school citizens gain a greater comprehension and consciousness of the 4R movement and the more prudent utilization of electricity by 94.4%. Furthermore, they acquire fresh perspectives concerning the energy-saving patterns of daily electrical energy use, thereby contributing to the betterment of society as a whole.